H’mong mustard seed production process - Ngo, Thi Hanh; Nguyen, Xuan Diep; Nguyen, Thi Lien Huong; Hoang, Minh Chau; Nguyen, Thi Phuong; Van, Lam Luong; Nabuuma, Deborah Sandra; Stomph, TjeerdJan; Swaans, Cornelis P.M. (2023)
The video documents the key steps in the production of H’mong mustard seed for farmers in Northern Vietnam. The training activities and this video were developed within the framework of the project “Integrated vegetable seed systems development in ethnic minority communities in Northern Vietnam for enhanced nutrition and income security”. A project part of the Netherlands - CGIAR Research Programme, funded by the Dutch Research Council (NWO). The video was also developed with support from the CGIAR Initiative on Nature-Positive Solutions for Shifting Agrifood Systems to More Resilient and Sustainable Pathways (NATURE+).